Determinants of Infertility among Married Women Attending Dessie Referral Hospital and Dr. Misganaw Gynecology and Obstetrics Clinic, Dessie, Ethiopia. (27th March 2020) - Bayu, Desalegn; Egata, Gudina; Kefale, Bereket; Jemere, Tadeg
Abstract : Background . Infertility is the inability to become pregnant after one year of sexual intercourse without the use of contraception. Epidemiological data suggest that 10 to 15% of couples around the world are suffering from infertility. The exact meaning of marriage is mainly fulfilled if the couple conceives and bears children. Failure of this often leads to unhappy married lives, divorces, and high levels of psychiatric morbidity. There is scarcity of data about determinants of infertility in Ethiopia. Therefore, the aim of this study is to identify the determinants of infertility among married women attending Dessie Referral Hospital and Dr. Misganaw gynecology and obstetrics specialty clinic, Dessie, Ethiopia, 2019. Methods . An institution-based case-control study was conducted on 281 participants. The participants were selected by a systematic random sampling technique. Data were collected using a structured interviewer-administered questionnaire. Data were entered into EpiData version 3.1 and exported to SPSS version 23 for analyses. Variables with p < 0.25 in bivariable logistic regression were entered into multivariable logistic regression. Odds ratio with its 95% confidence interval was estimated to measure the direction and strength of the association. The level of statistical significance was set at p < 0.05 . Results . The determinants of women's infertility were age at the first pregnancy (AOR = 2.89 ; 95% CI: 1.105, 7.564), age at menarche (AOR = 3.2 ; 95% CI: 1.278, 7.975), menstruation flow in days (AOR = 4.17 ; 95% CI: 0.062, 0.929), multiple sexual partners (AOR = 5.33 ; 95% CI: 2.124, 13.397), and history of STI (AOR = 2.79 ; 95% CI: 1.088, 7.159). Conclusion . Age at the first pregnancy, age at menarche, multiple sexual partners, number of days of menstruation flow, and history of STI were determinants of women's infertility. Infertility may bring about unhappy married lives, divorces, and high levels of psychiatric morbidity. Therefore, couples need to have heath education about risk factors for infertility.